1993
DOI: 10.1016/0167-4838(93)90254-o
|View full text |Cite
|
Sign up to set email alerts
|

Local variations in protein structure in the human eye lens: a Raman microspectroscopic study

Abstract: Confocal Raman microspectroscopy was used to monitor local and age-related changes in protein conformation in human eye lenses. In clear human lenses of varying age (range 17-80 years) spectra were recorded along the visual axis, using laser light of 660 nm wavelength. The Raman vibrations in the 650-1750 cm -1 spectral region were analyzed. Difference spectra between central core and different positions along the visual axis were calculated after calibration for protein content using the I(1450) cm-1 CH2/CH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 31 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Truscott and Augusteyn (1977) saw no loss of Trp in brunescent cataracts (144 nMol mg protein −" ), however, Kamei (1993) using magnetic circular dichroism found Trp values equivalent to 400 nMol mg protein −" , which decreased dramatically to 150 nMol mg −" protein in aged, dark brown lenses. Conversely, Smeets et al (1993) reported a marked increase in Trp content in the nucleus of the lens using Raman probe spectroscopy, which was even greater in aged human lenses and cataracts. Similar assays, however, showed a decrease in Trp in opaque compared to clear regions of cataract lenses (Duindem et al, 1998).…”
Section: -4835\98\090377j04 $3000\0mentioning
confidence: 94%
“…Truscott and Augusteyn (1977) saw no loss of Trp in brunescent cataracts (144 nMol mg protein −" ), however, Kamei (1993) using magnetic circular dichroism found Trp values equivalent to 400 nMol mg protein −" , which decreased dramatically to 150 nMol mg −" protein in aged, dark brown lenses. Conversely, Smeets et al (1993) reported a marked increase in Trp content in the nucleus of the lens using Raman probe spectroscopy, which was even greater in aged human lenses and cataracts. Similar assays, however, showed a decrease in Trp in opaque compared to clear regions of cataract lenses (Duindem et al, 1998).…”
Section: -4835\98\090377j04 $3000\0mentioning
confidence: 94%
“…The 'quest' is finding the cause of cataract, and for this, in vivo techniques could reveal the di#erent steps and changes in the lens. Raman spectroscopy is a unique tool in lens research since it provides structural information [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98] on proteins, amino acids (like Try, Trp, Phe), and sulphur bonds (-SH, S-S). The maturation process of the proteins in the lens cortex and nucleus can be studied in the intact lens, thus preventing oxidation of sulphydryls and protein disruption.…”
Section: Resultsmentioning
confidence: 99%
“…Shun-Shin et al [95] studied Christmas tree cataracts in human donor eyes and revealed that cystine is the most likely candidate for the formation of the Christmas tree needles. Smeets et al [96] described an age-related increase in tryptophan (ratios integrated peak 760:1450 cm 1 ) in the human lens core as an increase in the -sheet signals in the Amide I and II bonds. Chiou et al [97] determined in pigeon eye lenses that the secondary structures of -and -crystallins are mainly antiparallel -pleated sheet in nature.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Scanning electron microscopy of human lenses belonging to various age groups was employed for better understanding of tertiary and quaternary structure of protein fibers and membrane layers as well [2]. Raman microscopic study, also done on human lenses, concentrated on distribution of tyrosine and tryptophane amino acids in different sections of the lens [41]. What happens during cataract progression?…”
Section: Discussionmentioning
confidence: 99%